A multiobjective approach for energy consumption and link stability issues in ad hoc networks - De Rango, F.; Guerriero, F.; Marano, S.; Bruno, E. (IEEE communications letters, 2006)
This letter presents a novel analytical framework that jointly accounts the energy consumption and the link stability of mobile nodes. Two indexes for energy and link-lifetime are defined and a multiobjective integer linear programming problem has been defined. The proposed target function separates the energy and the link-stability contributions in order to differently change the weights of two opposite characteristics of mobile ad hoc networks. Some simulation results has been presented and the jointed impact of energy and stability has been evaluated.